Analisis dan Perancangan Sistem Informasi Pelayanan Pelanggan Berbasis Web pada King Kuphi - Arfah Anggina; Zul Fadli Lubis (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The development of information technology has had a significant impact on improving service quality in various sectors, including the culinary industry. KingKuphi, as a culinary business, still uses a manual system for ordering and managing customer data, resulting in various obstacles such as service delays and recording errors. This research aims to design a web-based customer service information system that can automate the ordering process, menu management, and payment transactions in an integrated manner. The development method used is the System Development Life Cycle (SDLC) with the Waterfall model, which includes the stages of requirements analysis, design, implementation, verification, and maintenance. The results show that the designed system can improve efficiency and accuracy in service management by providing digital menu features, automatic ordering, order notifications, and digital receipt printing. With the implementation of this system, the service process becomes faster, more structured, and more integrated between customers, waiters, the kitchen, and the cashier. This information system is expected to improve service quality and customer satisfaction, while supporting KingKuphi's operational management in a more modern and efficient manner.